Synthesis of enantiopure dihydropyranones: aldol-based ring expansion of dihydrofurans. - Donohoe, T; Raoof, A; Freestone, G; Linney, I; Cowley, A; Helliwell, M (2002)
[reaction: see text] The stereoselective Birch reduction of 3-methyl-2-furoic acids using a readily available chiral auxilairy is described; by coupling this process to an oxidative cleavage/aldol ring closure sequence we were able to produce highly functionalized and enantiopure dihydropyranones in high yield. This sequence has ample flexibility built into it, either by the use of different electrophiles during reductive alkylation or by subsequent derivatization of the dihydropyranone after ring expansion.